1976
DOI: 10.1111/j.1399-3054.1976.tb03942.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate, Ammonium and Kinetin Effects on Growth and Enzyme Activities of Paul's Scarlet Rose Callus

Abstract: Factorial experiments using the three variables nitrate, ammonium, and kinetin at six different concentrations each (nitrate 4.64 to 215 mM; ammonium 2.15 to 100 mM; and kinetin 0.1 to 4.64 mg/1) were set up to measure the effects of each of these factors, and their interactions, on the fresh weight, protein, and enzyme activities of callus of Paul's Scarlet Rose. Optimum fresh weight values were obtained with nitrate at 46.4 mM. Ammonium inhibited growth at concentrations above 2.15 mM, and kinetin had no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The possibility that nitrate reductase activity and protein synthesis were regulated to some extent by the availability of carbon supply to N30 cultures is suggested by the fact that zero nitrate reductase and maximum protein/ml culture on day 12 coincided with the final depletion of medium monosaccharides. This result agrees with the observation that little change in the activity of glutamine synthetase in Paul's Scarlet Rose callus cultures could be induced by varying the medium nitrate level between 10-100 mM (Caldas and Caldas, 1976). The profiles of enzyme activity were almost identical in N5 and N30 cultures under the conditions used in this experiment,indicating that the regulation of glutamine synthetase was not dependent upon medium nitrate availability.…”
Section: Relationship Of Enzyme Activities To Culture Growthsupporting
confidence: 90%
“…The possibility that nitrate reductase activity and protein synthesis were regulated to some extent by the availability of carbon supply to N30 cultures is suggested by the fact that zero nitrate reductase and maximum protein/ml culture on day 12 coincided with the final depletion of medium monosaccharides. This result agrees with the observation that little change in the activity of glutamine synthetase in Paul's Scarlet Rose callus cultures could be induced by varying the medium nitrate level between 10-100 mM (Caldas and Caldas, 1976). The profiles of enzyme activity were almost identical in N5 and N30 cultures under the conditions used in this experiment,indicating that the regulation of glutamine synthetase was not dependent upon medium nitrate availability.…”
Section: Relationship Of Enzyme Activities To Culture Growthsupporting
confidence: 90%
“…Cell cultures of several plants, including Paul's scarlet rose, have been shown to grow better with NO3-+ NH4+ than with NO3-alone (2,4,9,38). This was most pronounced when cells were grown in media possessing low concentrations of NO3-.…”
Section: Discussionmentioning
confidence: 99%
“…1A) Can. 3,4) showed that after day 3, NO3-+ NH4+ cultures achieved much higher NR activities than NO3-cultures. Downloaded from www.nrcresearchpress.com by Depository Services Program on 11/16/14 For personal use only.…”
Section: Cellular No3-mentioning
confidence: 94%